Antioxidant and Anti-inflammatory Activities of Diarylheptanoid from Etlingera calophrys Fruit - Karmilah, Karmilah; Yodha, Agung Wibawa Mahatva; Hamsidi, Rini; Daud, Nur Saadah; Malaka, Muhammad Hajrul; Musdalipah, Musdalipah; Sahidin, Sahidin (Molekul, 2024)
Diarylheptanoids compounds from the genus Etlingera have attracted widespread attention due to their various structural diversity and potential pharmacological effects. This is certainly an important part to continue to study, especially from Sulawesi endemic species, one of which is Etlingera calophrys. The fruit of E. calophrys is widely utilized in the Sulawesi community. The lack of information on the content of chemical compounds and their pharmacological activities, so the study is very important. Diarylheptanoid compounds were obtained by chromatography technique, molecular structure interpretation by spectroscopy technique while pharmacological activity was tested against radical scavenging as antioxidant and inhibition of protein denaturation as anti-inflammatory. Two diarylheptanoid compounds were successfully isolated from E. calophrys fruit namely 1-(3'-methoxy-4'- hydroxyphenyl)-7-phenyl- 3-heptanone and 1-(3'-methoxy-4'- hydroxyphenyl)-7-(4"-hydroxyphenyl)- 3-heptanone. Antioxidant properties showed very strong ability with IC50 values of 32.21 ± 0.42 and 21.64 ± 0.63 µg/mL, respectively, while anti-inflammatory properties were strongly shown by the compound with IC50 values of 25.71 ± 0.54 and 15.28 ± 0.66 µg/mL, respectively. The presence of diarylheptanoid content that has good pharmacological activity can support the used of E. calophrys as a nutraceutical source. Keywords: Anti-inflammatory, antioxidant, diarylheptanoid, Etlingera calophrys, fruit